Correction: Simultaneous synthesis of thioesters and iron–sulfur clusters in water: two universal components of energy metabolism. Issue 94 (13th November 2020) - Sanden, Sebastian A.; Yi, Ruiqin; Hara, Masahiko; McGlynn, Shawn E.
Abstract : Correction for 'Simultaneous synthesis of thioesters and iron–sulfur clusters in water: two universal components of energy metabolism' by Sebastian A. Sanden et al., Chem. Commun., 2020, 56, 11989–11992, DOI: ; 10.1039/D0CC07078A .